MEDIA POP UP BOOK TERHADAP PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA ANAK USIA SEKOLAH DASAR - Sulistyorini, Putri (THERA-DENT (jurnal terapis gigi dan mulut), 2023)
Background: Based on RISKESDAS data in 2013, the prevalence of dental and oral health disorders nationally was 25.9%, an increase compared to Riskesdas data in 2007. This reflects a low level of knowledge about oral and dental health, as well as the need for dental health education. One of them is providing dental health education using media such as pop up books. Objective: Knowing the influence of pop up book media to increase knowledge of dental and oral health in elementary school children of SDN Johar Baru 29 Central Jakarta. Method: Design descriptive analysis research with crosssectional approach method. A sample of 38 students using purposive sampling techniques. Result: significant value of 0.000 < 0.05, meaning that there is a relationship between pre-test and post-test variables. then it can be said if Ha is accepted. Conclusion: The influence of pop up book media to increase dental and oral health knowledge in students of SDN Johar Baru 29.